Acceptability of an orodispersible film compared to syrup in neonates and infants: a randomized controlled trial - Klingmann, Viviane; Pohly, Christoph Emanuel; Meissner, Thomas; Mayatepek, Ertan; Möltner, Andreas; Flunkert, Kathrin; Breitkreutz, Jörg; Bosse, Hans-Martin (European journal of pharmaceutics and biopharmaceutics, 2020)
Objectives - Reliable pediatric pharmacotherapy in all age groups requires the availability of age-appropriate drug administration. Orodispersible films (ODF) are a promising pediatric oral dosage form. ODFs would meet relevant targets: one dosage form matching the full range of pediatric patients, a minimum of non-toxic excipients, a stable drug formulation easily to be produced. However, there is a lack of reliable data on ODFs’ acceptability, swallowability and palatability, especially in young children. The primary objective was to demonstrate non-inferiority in acceptability of a drug-free ODF in comparison to glucose syrup in children aged below one year. Secondary objectives were swallowability and palatability of the two formulations. - Study design - The study was performed in an open, randomized, two-way cross-over design with three age groups: 2-28 days, 29 days-5 months, 6-12 months. 150 children (N = 50 per age group) were randomized to the order of receiving the ODF (2 × 3 cm) and age-adapted amounts of glucose syrup (0.5-3 mL). Deglutition and swallowing were assessed according to predefined evaluation criteria. The application of the formulations was documented by video to evaluate the palatability. - Results - The primary objective was confirmed: Non-inferiority of the acceptability of an ODF compared to syrup was demonstrated, even superiority of the ODF was shown (p < 0.0001). The secondary endpoints demonstrated positive results including the superior swallowability of the ODF in comparison to syrup (p < 0.0001). The palatability assessments were in favor of the ODF. - Conclusion - ODFs are a promising and safe alternative to liquid formulations, even for children of very young ages.